Motor inhibition in patients with Gilles de la Tourette syndrome: functional activation patterns as revealed by EEG coherence. - Serrien, D; Orth, M; Evans, A; Lees, A; Brown, P (2005)
There is considerable evidence that Gilles de la Tourette syndrome (TS) is due to frontal-striatal dysfunction. Here we determine whether adaptive cortical changes occur that might ameliorate the effects of this dysfunction. Specifically we test the hypothesis that increased interactions between selected cortical areas may help compensate through strengthened inhibition of inappropriate motor responses. To this end we recorded EEG in nine unmedicated patients with TS and nine age-matched healthy subjects during a variety of behavioural tasks related to motor inhibition. Functional connectivity between cortical areas was assessed by means of EEG coherence in the alpha frequency band (8-12 Hz). Elevated coherence was found between sensorimotor areas and the prefrontal and mesial frontal cortex during the acute voluntary suppression of tics. The same frontomesial network was overactive in TS patients compared with healthy subjects even when suppression of voluntary movement rather than tics was required during a Go-NoGo task. Behavioural performance in the Go-NoGo task was not different between patients and controls, confirming that the elevated frontomesial coherence in TS was likely to be adaptive rather than functionally disruptive. It is concluded that the gain in inhibitory frontomesial cortical networks is adaptively heightened in TS, and that the same network can also be engaged in the voluntary suppression of tics.